Probing the photochemistry and photophysics of organic and inorganic chromophores - Reynolds, Katherine Elizabeth Anne (2020)
Chapter 1 This Chapter gives an introduction to the techniques used within this Thesis. A brief outline is given on time resolved infrared (TRIR), the pump-probe method that has been utilised throughout this Thesis to investigate the photophysical, and photochemical properties of the complexes of interest. Chapter 2 The photophysical and photochemical properties of [Re(CO)4(bpy)][PF6] have been probed in Chapter 2, with both picosecond and nanosecond TRIR run in CH2Cl2 and CH3CN at two dierent excitation wavelengths. [Re(CO)4(bpy)][PF6] exhibits interesting photochemical behaviour, where a CO ligand can be easily dissociated by excitation at 355 nm. Prior to the work discussed in Chapter 2, only one time-resolved measurement had been reported in the literature, which proposed a mixed state was populated, that subsequently lead to the photodissociation of CO. However, no ultrafast studies have been conducted which could help to determine the nature of the excited states formed. The work within this Chapter probes the nature of the excited states, with time-dependent density functional theory calculations (TD-DFT) to support the assignment of the excited state. It was found that when [Re(CO)4(bpy)][PF6] is excited at 355 nm in either CH2Cl2 or CH3CN two excited states are populated siv multaneously, with one of the states leading to the photodissociation of CO. With the experimental results and the TD-DFT calculations, it was determined that both these excited states have not only metal to ligand charge transfer (MLCT) character, but also inter ligand charge transfer (ILCT) leading to the formation of a mixed state. The MLCT character of these two mixed ILCT/MLCT excited states dictates the photodissociation of CO, as determined by the TD-DFT calculations which studied the movement of electron density throughout the molecule. The observation of this second mixed ILCT/MLCT state has not previously been reported, and is thought to be the state responsible for the emission observed from [Re(CO)4(bpy)][PF6]. The lifetime of the two states are very dierent, with the emissive state decaying faster (· = 100 ns) than the other state mixed state, which decayed (· = 3 µs) to form a solvated photoproduct. When [Re(CO)4(bpy)][PF6] is excited at 266 nm, only one mixed ILCT/MLCT state is observed which decayed ( · = 900 ns) to form a solvated photoproduct via the photodissociation of CO. The observation of two excited states following a 355 nm excitation and one excited state following a 266 nm excitation was seen for both CH2Cl2 and CH3CN. Both solvated photoproducts, [Re(CO)3(bpy)(CH2Cl2)] and [Re(CO)3(bpy)(CH3CN)][PF6] were observed in the TRIR spectra, following the decay of a mixed ILCT/MLCT excited state. Preliminary spectroelectochemical investigations also found that it is possible to electrochemically induce CO loss, resulting in the formation of two stable rhenium tricarbonyl complexes, Re(CO)3(bpy)Cl and Re(CO)3(bpy)(CH3CN)][PF6]. Chapter 3 This Chapter probed the photophysical and photochemcial properties of Re(CO)4(dppz)] [PF6] with TRIR, to elucidate the nature of the excited states. Changing the –-diimine vi ligand was also investigated to see if the photochemical properties can be altered. From the literature and work in Chapter 2, it is known that a rhenium tetracarbonyl centre coordinated to a –-diimine ligand can undergo CO loss to form a solvated photoproduct. Re(CO)4(dppz)] [PF6] was probed in CH2Cl2 and CH3CN, and excited at 355 and 266 nm. When excited at 355 nm, Re(CO)4(dppz)][PF6] formed an initial excited state that decayed away (· = 100 ps) forming a second excited state which was a long lived mixed ILCT/MLCT state (· = 3 µs). This mixed excited ILCT/MLCT state decayed back down to the ground state, and does not result in the formation of the solvated photoproduct in either solvent. Using TD-DFT calculations the nature of these two states was determined, with both appearing to be a mixed ILCT/MLCT excited state with varying degrees of ‘Re ≠æ phen’ character. When the excitation energy was increased to 266 nm, dierent photophysical properties were observed for the two solvents. In CH2Cl2 upon excitation a ILCT(phen) excited state was seen, which decayed (· = 80 ps) to form a ILCT/MLCT mixed excited state. This ILCT/MLCT mixed excited state decayed (· = 2 µs) to form a solvated photoproduct, Re(CO)3(dppz)(CH2Cl2)] which is not as stable as the photoproduct observed for [Re(CO)4(bpy)][PF6]. However, in CH3CN upon excitation at 266 nm an inital excited state was populated which decayed to form a ILCT/MLCT state (· = 55 ps). This ILCT/MLCT excited state decayed (· = 1.4 µs) back down to the ground state, and no formation of photoproduct was observed. This suggested that the photochemical properties of Re(CO)4(dppz)][PF6] are both solvent and wavelength dependent. Along with the photophysical and photochemcial properties, the spectroelectrochemistry was also probed. It was found that a stable tricarbonyl product was formed following the dissociation of CO. Therefore, Re(CO)3(dppz)Cl and Re(CO)3(bpy)(CH3CN)][PF6] can be obtained electrochemically. vii Chapter 4 A group of unique rylene rotaxane handcu complexes were investigated in Chapter 4. These rotaxane handcu complexes are a group of PDI and NDI monomers and dimers that have been ‘handcued’ together to form non-covalently bound dimers. The photophysics of PDI monomers and covalently bound PDI dimmers have been previously reported, the photophysical properties of non-covalently bound PDI dimers remain unknown. Using ultrafast techniques, transient absorption (TA) and TRIR, we have probed, for the first time, the photophysics of a non-covalently bound handcu PDI dimer. The two PDI monomers were probed at 520 nm in CH2Cl2 and both formed 1PDI excited states, with PDI-2 being shorter lived (· = 80 ps ) than PDI-1 (· = 400 ps ). In contrast, the NDI monomer, NDI-1 , was excited at 380 nm which resulted in the formation of a 1NDI excited state, which quickly decayed (· = 0.6 ps) to form a NDI–• species. This NDI–• then decayed (· = 20 ps) to form a long lived 3NDI excited state. When the PDI monomers and NDI monomer are ‘handcued’ together there is a change to the photophysical properties. The two dimer complexes were probed at 520 nm in CH2Cl2, with PDI/PDI dimer handcu complex resulting in the formation of an excimer state which has a lifetime of · = 650 ps. The NDI/PDI dimer saw the formation of an ion pair with both a NDI–• and PDI–• species being populated following the decay of a 1PDI excited state (· = 2 ps). The NDI–• species decayed away at a faster rate (· = 220 ps) than the PDI–• species (· = 900 ps). As well as these three monomers and two handucu dimers, a PDI rotaxane was also probed. This PDI handcu complex has a pillar-[5]-arene wheel located on the alkly chain between the end group and the PDI core. When excited at 532 nm, a viii 1PDI excited state is formed, which undergoes a charge transfer (CT) process (· = 10 ps) to form a PDI–• species. Both a 1PDI excited state and a PDI–• species are observed which decay with dierent lifetimes. The 1PDI excited state decayed faster (· = 80 ps) than the PDI–• species (· = 200 ps). This illustrated that incorporating an electron rich group onto a PDI monomer can result in a charge separated state. Chapter 5 Chapter 5 investigates the synthesis and characterisation of the fluorinated photosensitive rhenium –-diimine dye, fac-Re(CO)3(bpy – RF 8 )Cl. A full spectroscopic study was conducted for fac-Re(CO)3(bpy – RF 8 )Cl in range of solvents, with comparisons made to a non-fluorinated analogue; fac-Re(CO)3(dnb)Cl. The photophysical properties of the two complexes were also investigated, in both polar and non-polar solvents. The solubilities of two perfluorinated complexes were investigated fac-Re(CO)3(bpy – RF 8 )Cl and fac-Re(CO)3(bpy – RF 10)Cl, and it was found that fac-Re(CO)3(bpy – RF 10)Cl was more soluble in perfluorinated media than the shorter chain analogue. The luminescence was probed, and for fac-[Re(CO)3(dnb)Cl] when the polarity of the solvent is decreased there is a red shift of the emission peak to higher energy, this is indicative of positive solvatochromism. However, [Re(CO)3(RF8(CH2)3 – bpy)Cl] exhibited a blue shift of the emission peak to lower energy with lowering polarity, which is consistent with negative solvatochromism. When the concentration of fac-Re(CO)3(bpy – RF 8 )Cl was decreased, a switch in the solvatochromism was observed, with a low concentration resulting in positive solvatochromism. This suggests that the long perfluorinated chains are aggregating in solution. A TRIR spectroscopic investigation was carried out for fac-Re(CO)3(bpy – RF 8 )Cl and fac-Re(CO)3(dnb)Cl in CH3CN. The ps-TRIR and ns-TRIR of fac-Re(CO)3(bpy – RF 8 )Cl ix in acetonitrile gave a 3MLCT excited state (· = 34 ns). The ps-TRIR and ns-TRIR of Re(CO)3(dnb)Cl in CH3CN also exhibited a 3MLCT excited state (· = 36 ns), indicating that the long perfluorinated chain on the complex is not influencing the excited state. As well as the photophysical properties, the photochemcial properties of fac-Re(CO)3(bpy – RF 10)Cl were probed at 266 nm in CH2Cl2 with the aim of forming a dicarbonyl species, instead a 3MLCT excited state (· = 57 ns) was seen and no formation of the dicarbonyl species was observed. This supports the theory that perfluorinated chains are aggregating in solution. Chapter 6 The summaries and future work of the results obtained from the work in this Thesis is given in this Chapter. It discuses the implications that have arisen from these results and areas of research that could be investigated in the future. Chapter 7 The experimental methods and spectroscopic techniques used throughout this Thesis are described in this Chapter. This includes detailed descriptions of the equipment used, along with procedures and materials used.